Evaluación de un híbrido de romanesco (Brassica oleracea var. botrytis L.) A tres Métodos de control, aplicados a dos dosis, para (Plasmodiophora brassicae Wor.)”, en la Parroquia San Buenaventura, Cantón Latacunga, Provincia de Cotopaxi 2015 - Chancúsig Panchi, Diana Maribel (2015)
This research entitled: "Evaluation of a hybrid romanesco (Brassica oleracea L. var botrytis.) Three control methods applied two doses to (Plasmodiophora brassicae Wor.)", San Buenaventura Parrish, Latacunga Canton, Cotopaxi Province 2015 period, it aimed was to evaluate a hybrid of Romanesque and determine the most efficient method of control and the best dosage. The results of the research was: the CaCO3 product showed better efficiency with the implementation of the dose one (1 lt / ha). Take up the second place of the product Juwel Top doses one (1 lt / ha) and finally AgriSafe, in regard to the treatment the better was p1d1 (CaCO3 + dose 1) to report 60,647.87 kg / ha of performance, a production cost of $ 5,195.32 / ha, resulting in a cost benefit of $ 2.33. Unlike treatment corresponding to P3D0 (Control + AgriSafe) with a yield of 40,678.64 kg / ha and cost benefit of $ 1.57 being the lowest. The researcher recommend to sow hybrid CaCO3 Veronica and use the product, to free the nutrients in the soil and encourage greater root mass, also reduce the incidence of the pathogen (Plasmodiophora brassicae) that does not tolerate alkaline pH as an alternative method of control.